ESP AND STUDENTS’ NEEDS IN LEARNING ENGLISH FOR PHARMACY - Talipov Begzod Botirovich; Akhmedova Dilnoza Anvarovna; Toshkhonov Mahamadali Turdaliyevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article aims to discover the needs of pharmacy students at IPER as input to design an ESP syllabus. The needs analyses were conducted by distributing questionnaires to and interviewing the respondents. The responses were analyzed based on a comprehensive concept of need analysis proposed by scholars. The findings showed that most students consider themselves poor in vocabulary and weak in speaking, listening, writing, and pronunciation. Hence, it is crucial to improve their skills to enable them from communicating effectively with foreign patients and avoiding misunderstandings that may happen when interacting with foreign patients. Therefore, developing an appropriate ESP syllabus for pharmacy and industrial pharmacy courses could be possibly developed based on these findings and the theory of material development.